2006
DOI: 10.1002/uog.2693
|View full text |Cite
|
Sign up to set email alerts
|

The conservative management of cervical ectopic pregnancies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
1
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 37 publications
1
73
1
12
Order By: Relevance
“…We found advanced maternal age was the only risk factor that was significantly associated with extratubal gestations compared to pregnant women with tubal gestations. Similar findings were also reported in other studies: Median age of 37 years in cervical pregnancies, 16 mean age of 35 years in cesarean scar pregnancies 17 and mean age of 31.2 years in abdominal pregnancies. 18 Highest rates of ectopic pregnancies occurred in women aged 35 to 44 years.…”
Section: Discussionsupporting
confidence: 92%
“…We found advanced maternal age was the only risk factor that was significantly associated with extratubal gestations compared to pregnant women with tubal gestations. Similar findings were also reported in other studies: Median age of 37 years in cervical pregnancies, 16 mean age of 35 years in cesarean scar pregnancies 17 and mean age of 31.2 years in abdominal pregnancies. 18 Highest rates of ectopic pregnancies occurred in women aged 35 to 44 years.…”
Section: Discussionsupporting
confidence: 92%
“…According to the same Hung et al meta-analysis, overall success rate using single dose of MTX was 62%, although when cardiac activity was not present 91% of cases were successful and when cardiac activity was present -only 40%. More recent studies show overall MTX success rate as high as 81.3-83% [18]. More advanced pregnancies, when cardiac activity is discovered, should be treated with MTX and potassium chloride in addition to cause fetal death and facilitate resorption of larger gestational sac [19].…”
Section: Discussionmentioning
confidence: 99%
“…medical managements in the from of systemic or intraamniotic MTX, with or without intra-amniotic potassium chloride administration criteria for conservative treatment are patient should be haemodynamically stable, have no haemoperitonium on TVS scanning , have normal kidney and liver function 21 . Additional specific requirements for expectant managemants are no fetal cardiac activity 22 . Serum hCG level were measured on day 1, 4 and 7 with day 1 being the day of first injection of MTX.…”
Section: Discussionmentioning
confidence: 99%
“…A review of English literature from 1911 to1994 found 39 cervical ectopic pregnancies and 29 patient were treated conservatively 27 . Out come of most of the pregnancies after cervical ectopic will lead to term deliveries but there is possibility of preterm labour in such cases [22][23] .…”
Section: Discussionmentioning
confidence: 99%